2004
DOI: 10.3748/wjg.v11.i5.733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamate on inflammatory responses of intestine and brain after focal cerebral ischemia

Abstract: AIM:To study the modulation of glutamate on post-ischemic intestinal and cerebral inflammatory responses in a ischemic and excitotoxic rat model. METHODS:Adult male rats were subjected to bilateral carotid artery occlusion for 15 min and injection of monosodium glutamate intraperitoneally, to decapitate them at selected time points. Tumor necrosis factor alpha (TNF-) level and nuclear factor kappa B (NF-B) activity were determined by enzyme-linked immunosorbant assay (ELISA) and electrophoretic mobility shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 26 publications
1
23
0
2
Order By: Relevance
“…It has been shown that the glutamate system is involved in the pathogenesis of I/R in brain and intestine [30] . Glutamate release and NMDA receptor activation induces nitric oxide, and other free radicals that cause tissue injury [31] .…”
Section: Issnmentioning
confidence: 99%
“…It has been shown that the glutamate system is involved in the pathogenesis of I/R in brain and intestine [30] . Glutamate release and NMDA receptor activation induces nitric oxide, and other free radicals that cause tissue injury [31] .…”
Section: Issnmentioning
confidence: 99%
“…Amino acids (e.g., glutamate, glutamine, arginine) and/or small peptides are involved in gene and protein expression, and are associated with PPARγ, NF-κB, and antioxidant defense (Xu et al 2005;Sato et al 2006;Erdmann et al 2008;Ringseis et al 2009;White et al 2009;Wu 2009;Brasse-Lagnel et al 2010;Coeffier and Dechelotte 2010). Small (up to tripeptides) and large (up to 51 amino acids) peptides, possibly including GGC, can be taken up intact through plasma membranes via Na + -coupled peptide transporter 1 (PEPT1) and transporter 2 (PEPT2) in various tissues, such as intestine, brain, eye, kidney, lung, mammary gland, and prostate (RubioAliaga et al 2003;Zhou et al, in press;Chothe et al, 2011), and produce biological effects at the tissue levels (Roberts et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Amino acids (e.g., glutamate, glutamine, arginine) and/or small peptides are involved in gene and protein expression, and are associated with PPARγ, NF-κB, and antioxidant defense (Xu et al 2005;Sato et al 2006;Erdmann et al 2008;Ringseis et al 2009;White et al 2009;Wu 2009;Brasse-Lagnel et al 2010;Coeffier and Dechelotte 2010). Small (up to tripeptides) and large (up to 51 amino acids) peptides, possibly including GGC, can be taken up intact through plasma membranes via Na + -coupled peptide transporter 1 (PEPT1) and transporter 2 (PEPT2) in various tissues, such as intestine, brain, eye, kidney, lung, mammary gland, and prostate (RubioAliaga et al 2003;Zhou et al, in press;, and produce biological effects at the tissue levels (Roberts et al 1999).…”
Section: Discussionmentioning
confidence: 99%